Pilotprojekt Gropiusstadt : Jahrbuch 2005. (Berlin : Kulturnetzwerk Neukölln Berlin, 2005)
Aichner, Wolfgang ; Albrecht-Boer, Susanne ; Böning, Andrea ; Désert, Jean-Ulrick ; Dessin, Anke ; Döscher, Heike ; Eden, Irena ; Elffriede ; Heerlein, Jan ; Hohmann, Katharina ; Jensen, Jacob ; Jesch, Birger ; Kaltwasser, Martin ; Köberling, Folke ; Lernout, Stijn ; Low, Antonia ; McGeorge, Eline ; Mohr, Ulrike ; Morita, Satoshi ; Neuhaus, Gertrud ; Niessing, Marion ; Niscino, Tazro ; Olbrich, Jürgen O. ; Ostendorf, Ulla ; Rinck, Jürgen ; Ross, Monica ; Schamp, Matthias ; Spielhagen, Petra ; Takahashi, Tomoko ; Timm, Thea ; Trahan, Carl ; Wojcik, Jaroslaw
zie kast losse tijdschriften
Duits
boek